Influence of Stress States on Forming Hybrid Parts with Sheet Metal and Additively Manufactured Element - Hafenecker, Jan; Papke, Thomas; Merklein, Marion (Journal of Materials Engineering and Performance, 2021)
Hybrid parts with additively manufactured elements (AME) combine the advantages of two or more manufacturing processes, e.g., forming and additive manufacturing (AM), and thus offer a solution to the increasing demands of industrial trends such as personalized mass production. Despite their advantageous properties, research in this field still lacks in clear classification and process interactions. Due to the strong influence of the AME on the formability of hybrid parts, the combination of laser-based powder bed fusion (PBF-LB) with subsequent sheet metal forming is examined in this paper. Therefore, cylindrical functional elements are built up on sheet metal and the resulting hybrid components are subsequently formed. Common forming processes such as bending, stretch forming and deep drawing are compared in regard to the different stress states. The results show a reduction in formability for hybrid components compared to conventional sheet metal materials. Reasons found are geometrical properties, gradients of mechanical properties and induced stresses. Consequently, requirements for the additive manufacturing process regarding a subsequent forming process are outlined. Namely, the gradient of mechanical properties should be smoothened, residual stresses kept low and the design of AMEs should avoid stress concentration.<br
Keywords: additive manufacturing; hybrid material; modelling and simulation; sheet metal formability; titanium